До питання передумов військових конфліктів у контексті інформаційної безпеки та її вплив на свідомість громадян - Рудянин, Іван Петрович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The guarantee of national security of any state is its actual security, integrity and inviolability of borders, as well as economic and political independence in modern conditions. At the beginning of the russian military invasion of Ukraine, the world society discovered a new type of external threats in the form of “hybrid” wars that affect key segments of the country’s life. A prerequisite for an armed conflict is the detailed preparation of the is mean “groundwork” for the future intervention of foreign armed forces on a certain territory. This is to create a favorable background for the aggressor country in the theater of future hostilities.